Risk analysis of microorganisms in common food spices - Tang, Xiaoyang (Frontiers in Microbiology, 2025)
Spices play a ubiquitous role in the food industry, imparting distinctive flavors and exhibiting antibacterial properties. Nonetheless, microbial contamination and residues present persistent challenges to food safety within this sector. The systematic tracking of microbial input datasets in spices holds significant guiding implications and economic value for microbial control and risk assessment in the food industry. Furthermore, it serves as a cornerstone for developing early safety warning systems and precise prevention and control frameworks in spice processing. This paper, following a structured literature review methodology, conducts an in-depth analysis of microbial (bacterial and fungal) contamination across 41 commonly utilized spices. It elucidates the exposure risks associated with significant pathogenic and spoilage microorganisms prevalent in spices, categorizes the risk levels pertaining to spices and their corresponding microbial pollution profiles, and delineates an early warning framework for microbial contamination in spices. These findings furnish crucial insights for formulating control strategies targeting microorganisms in the spice sector and identifying key microbial control points within food processing operations.Systematic review registrationhttps://myfrontiers.frontiersin.org/projects/submission/1549719.